Exploring why people with SMI smoke and why they may want to quit: baseline data from the SCIMITAR RCT. Issue 5 (3rd July 2015) - Peckham, E.; Bradshaw, T. J.; Brabyn, S.; Knowles, S.; Gilbody, S.
Abstract : Accessible summary: People with severe mental ill health are up to three times more likely to smoke than other members of the general population. Life expectancy in this client group is reduced by up to 30 years, and smoking is the single most important cause of premature death. The aim of this study was to explore why people with severe mental ill health smoked and why they might want to stop smoking or cut down on the amount of cigarettes that they smoked. The study found that people with severe mental ill health are motivated to cut down or stop smoking, and this is mainly due to concerns about their own health. The reasons people gave for smoking were to relieve stress, to help relax and for something to do when they are bored. Health professionals should offer evidence supported smoking cessation therapy to people with severe mental ill health. In addition to standard National Health Service smoking cessation treatments such as pharmacotherapy and behavioural support. Practitioners should help people with serious mental ill health to identify meaningful activities to relieve boredom and challenge any incorrect beliefs they hold that smoking helps relaxation and relieves stress. Abstract: Smoking is the single most preventable cause of premature mortality for people with serious mental ill health (SMI). Yet little is known about the reasons why service users smoke or what their motivations for quitting might be. The aim of this paper is to explore smoking behaviours, reasons for smoking and motivations for cutting down/stopping smoking in individuals with SMI who expressed an interest in cutting down or stopping smoking. Prior to randomization, the smoking behaviours and motivations for wanting to cut down or stop smoking of participants in a randomized trial were systematically assessed. Participant's primary reasons for continuing to smoke were that they believed it helped them to cope with stress, to relax and relieve boredom. Participant's main motivations for wanting to cut down or stop smoking were related to concerns for their own health. Previous attempts to stop smoking had often been made alone without access to evidence supported smoking cessation therapy. Future recommendations include helping people with SMI to increase their activity levels to relieve boredom and inspire confidence in their ability to stop smoking and challenging beliefs that smoking aids relaxation and relieves stress.